Regulation of the Total Cell Surface Area in Dividing Dictyostelium Cells - Tanaka, Masahito; Fujimoto, Koushiro; Yumura, Shigehiko (Frontiers in Cell and Developmental Biology, 2020)
When a cell divides into two daughter cells, the total cell surface area should increase. There are two models for membrane supply to support cell division: (1) unfolding of small surface membrane reservoirs such as microvilli or wrinkles and (2) exocytosis of intracellular vesicles. Here, we precisely measured the total cell surface area in dividing Dictyostelium cells, flattened by the agar overlay that eliminated the complexity of unfolding surface membrane reservoirs. Because the cells divided normally under the agar overlay, unfolding of surface membrane reservoirs was not required for cell division. Under the agar overlay, the total cell surface area slightly decreased from the interphase to the metaphase and then increased about 20% during cytokinesis. Both endocytosis and exocytosis were suppressed in the early mitotic phase but recovered during cytokinesis. The imbalance of endocytosis and exocytosis could contribute to the changes observed in the cell surface area. Clathrin-dependent endocytosis was also substantially suppressed during cytokinesis, but contrary to previous reports in cultured animal cells, it did not significantly contribute to the regulation of the cell surface area. Furrowing during cytokinesis was indispensable for the cell membrane increment, and vice versa.